ChemInform Abstract: Enzymatic Conversion of Carbon Dioxide. Issue 42 (October 2015) - Shi, Jiafu; Jiang, Yanjun; Jiang, Zhongyi; Wang, Xueyan; Wang, Xiaoli; Zhang, Shaohua; Han, Pingping; Yang, Chen
Abstract Review: 49 refs.